1995
DOI: 10.1016/0092-8674(95)90290-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and mutational analysis of human uracil-DNA glycosylase: Structural basis for specificity and catalysis

Abstract: Crystal structures of the DNA repair enzyme human uracil-DNA glycosylase (UDG), combined with mutational analysis, reveal the structural basis for the specificity of the enzyme. Within the classic alpha/beta fold of UDG, sequence-conserved residues form a positively charged, active-site groove the width of duplex DNA, at the C-terminal edge of the central four-stranded parallel beta sheet. In the UDG-6-aminouracil complex, uracil binds at the base of the groove within a rigid preformed pocket that confers sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
326
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 355 publications
(344 citation statements)
references
References 49 publications
15
326
2
1
Order By: Relevance
“…AtUNG conserves critical residues involved in substrate recognition and catalysis in Family-1 enzymes (1). Amino acids Tyr-175 and Asn-231 correspond to residues that contribute to selectivity against other pyrimidines, including thymine, in human UNG (19). The conserved Leu-299 is involved in nucleotide flipping by penetrating in the minor groove and expelling uracil (19), and Asp-173 acts as a general base that activates water for attack of the N-glycosyl bond (20).…”
Section: Resultsmentioning
confidence: 99%
“…AtUNG conserves critical residues involved in substrate recognition and catalysis in Family-1 enzymes (1). Amino acids Tyr-175 and Asn-231 correspond to residues that contribute to selectivity against other pyrimidines, including thymine, in human UNG (19). The conserved Leu-299 is involved in nucleotide flipping by penetrating in the minor groove and expelling uracil (19), and Asp-173 acts as a general base that activates water for attack of the N-glycosyl bond (20).…”
Section: Resultsmentioning
confidence: 99%
“…The elucidation of the crystal structures and mutational studies of human [70,[81][82][83] and herpes-viral [84] UDGs have demonstrated the mechanism for the selective binding of uracil over the structurally closely related normal pyrimidine in DNA, and have revealed the catalytic mechanism. DNA binds along a positively charged groove in the enzyme, but the tight-fitting uracil-binding pocket located at the base of this groove is too deep and narrow to allow binding of DNA-uracil unless it is ' flipped out ' of the DNA helix.…”
Section: Structure-function Analyses Of Udgmentioning
confidence: 99%
“…S3). For the purpose of clarity, the names of the human UNG mutants were kept the same as described (27,35). To express AID and UNG from a single retroviral vector, hAID was first cloned into EcoRI and SalI1 sites of the retroviral expression vector pFB-IRES-GFP.…”
Section: Methodsmentioning
confidence: 99%